Micro-arc oxidation (MAO) and its potential for improving the performance of titanium implants in biomedical applications - Wen, Xueying; Liu, Yan; Xi, Fangquan; Zhang, Xingwan; Kang, Yuanyuan (Frontiers in Bioengineering and Biotechnology, 2023)
Titanium (Ti) and its alloys have good biocompatibility, mechanical properties and corrosion resistance, making them attractive for biomedical applications. However, their biological inertness and lack of antimicrobial properties may compromise the success of implants. In this review, the potential of micro-arc oxidation (MAO) technology to create bioactive coatings on Ti implants is discussed. The review covers the following aspects: (1) different factors, such as electrolyte, voltage and current, affect the properties of MAO coatings; (2) MAO coatings affect biocompatibility, including cytocompatibility, hemocompatibility, angiogenic activity, corrosion resistance, osteogenic activity and osseointegration; (3) antibacterial properties can be achieved by adding copper (Cu), silver (Ag), zinc (Zn ) and other elements to achieve antimicrobial properties; and (4)MAO can be combined with other physical and chemical techniques to enhance the performance of MAO coatings. It is concluded that MAO coatings offer new opportunities for improving the use of Ti and its alloys in biomedical applications, and some suggestions for future research are provided.